Ferula groessingii (Apiaceae), a new synonym of Ferula licentiana var. tunshanica - Lei Yang; Wen-Jun Li (PhytoKeys)
A comprehensive evaluation of the diagnostic characters employed in distinguishing Ferula groessingii from F. licentiana var. tunshanica has led to the conclusion that the two taxa are indeed conspecific. As a result, F. groessingii is hereby recognized as a new synonym of F. licentiana var. tunshanica. This reclassification is supported by a comprehensive comparison of taxonomic features, morphological evidence, and distribution data. The study confirms that key morphological traits including plant height, a hairy coat of stems and leaves, number of inflorescences, and fruit vittae, are critical for the identification of this species complex.